PERMAINAN MONOPOLI BERBASIS METODE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) SEBAGAI MEDIA PEMBELAJARAN BIOLOGI MATERI SISTEM PENCERNAAN - Ika Suci Rahayu; Handoko Santoso; Triana Asih (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2020)
Learning media is an intermediary used for student learning tools. Students inthe learning process feel bored with the delivery of material. Submission ofmaterial that is less varied causes students to be less active so that theunderstanding of the material is not optimal. The teacher uses torso media inlearning but the learning outcomes are still less than KKM (Minimumcompleteness criteria). One way to overcome this is by developing monopolygames as biology learning media. Monopoly game is a type of board gamethat aims to accumulate wealth and control complexes on a monopoly boardgame. The teacher can modify the shape of this monopoly board game (astuti:2014). The use of instructional media appropriately and varied can overcomethe passive attitudes of students and overcome boredom during the learningprocess. Monopoly Game Development as a Biology Learning Media Materialof Digestive System Based on STAD (Student Teams Achievement Division)Method is interesting to be studied.The purpose of this research is to producea media product in the form of a decent monopoly game for learning biologyof the human digestive system. This type of research is the development of the4D model (Define, Design, Develop, Desseminat or 4 P called defining,planning, developing and disseminating. Monopoly Game Development as aBiological Learning Media for Digestive System Material using the STAD(Student Teams Achievement Division) method. Media development wasvalidated by biology lecturers and subject teachers as media design expertsand the material was subsequently tested on grade XI students.The results ofrecapitulation of expert validation and student trials showed very goodcriteria, namely: (a) Aspects of media design reached an average score of88.7% (b) Aspects of material reached an average score of 89.1% and (c)trials learners reach a score of 90.25%. This study can be concluded that theMonopoly Game as a Learning Media for Biology of the Digestive SystemMaterial Based on the STAD Method (Student Teams Achievement Division) issuitable for the learning process facilities.